M182. EFFECTIVENESS OF COORDINATED SPECIALTY CARE (CSC) DELIVERED VIA TELE-HEATH COMPARED TO THE STANDARD CSC CLINIC-BASED MODEL. (18th May 2020) - Breier, Alan; Lurkins, John; Vohs, Jennifer; Gaunnac, Megan; Francis, Michael
Abstract: Background: There is a growing body of evidence suggesting that specialized early intervention (EI) programs deliver superior outcomes for individuals with early phase psychosis. Coordinated Specialty Care (CSC) is a recovery-oriented EI treatment program that employs multi-disciplinary team based care with high provider to patient staffing ratios and promotes shared decision making. CSC services are primarily provided in health care clinics. An alternative to "in clinic" service models is tele-health (TH) where clinical care and team interactions occur remotely through TH platforms. The advantages of this model may include reduced costs, bridging geographical distances, decreased stigma and increased flexibility for when and where therapeutic sessions occur. The purpose of this study is to compare the effectiveness of CSC delivered through TH (CSC-TH) versus the standard, clinic-based CSC model (CSC-Clinic). Methods: A TH network was established in Indiana, USA to provide statewide CSC services. A "hub" team, comprised of a psychiatrist, therapist, team leader, nurse and data manger, was located in Indianapolis, IN and four "spoke" sites (Ft. Wayne, Anderson, Gary and Bloomington IN), were established across the State. All hub team services were delivered remotely through VIDYO, a leading, HIPPA compliant TH platform which was used on hand-held devices for care deliver in the subjects' homes, as well as in local CMHCs. The standard clinical CSC program (CSC-Clinic), termed Prevention and Recovery Center (PARC), was located in Indianapolis, IN and all services were obtained through in-person clinic visits. Both the CSC-TH and CSC-Clinic programs employed identical inclusion criteria (16 – 30 years; within 3 years of psychosis onset; and non-substance induced psychotic disorder), assessment instruments, OnTrackNY training for all treatment staff, and outcome measures. Both programs conducted weekly team meetings where all patients were reviewed. Both programs were assessed for fidelity to the CSC model. All CSC patients were newly enrolled over the same treatment period. Data was collected at baseline, 3 months and 6 months. The outcome measures included engagement (drop outs), use of acute services (ER, hospitalization), illness severity (CGI-S), and MIRECC GAF symptoms, occupation/school function and social function. Ratings were independently determined through consensus of the respective treatment teams. Results: Thirty-one early phase subjects were enrolled in the CSC-TH and 89 in the CSC-Clinic programs. Analyses demonstrates that CSC-TH was associated with significant and trend level superiority compared to CSC-Clinic for better engagement (3-month: X2=2.89, p=0.09; 6-month: X2=3.12, p=0.05); less use of acute services (3-month: X2= 6.62, p=0.01; 6-month: X2 =7.17, p=0.07); lower MIRECC GAF symptoms (3-month: t=3.2, p=0.002), improved occupation/school function (3-month: t=3.02, p=0.003) and social function (t=3.18, p=0.002). No group differences were found for CGI-S ratings. Discussion: These results suggest that CSC-TH was associated with better outcomes compared to CSC-Clinic on key variables. Important caveats, including lack of randomization and blinded ratings, will be discussed. Future studies needed to further evaluate the role of TH in EI programs will be proposed.